2009
DOI: 10.3767/003158509x418925
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic taxonomy of the heat resistant ascomycete genus <I>Byssochlamys</I> and its <I>Paecilomyces</I> anamorphs

Abstract: Byssochlamys and related Paecilomyces strains are often heat resistant and may produce mycotoxins in contaminated pasteurised foodstuffs. A comparative study of all Byssochlamys species was carried out using a polyphasic approach to find characters that differentiate species and to establish accurate data on potential mycotoxin production by each species. Phylogenetic analysis of the ITS region, parts of the β-tubulin and calmodulin genes, macro- and micromorphological examinations and analysis of extrolite pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 52 publications
7
126
0
1
Order By: Relevance
“…ITS sequencing and phylogenetic analysis indicated that the isolate (PaePR) obtained in this study was clustered with its teleomorph, B. nivea. Samson et al (2009) verified by phylogenetic analyses that the genus Byssochlamys includes nine species, five of which form teleomorphs, i.e., B. fulva, B. lagunculariae, B. nivea, B. spectabilis and B. zollerniae, whereas four are asexual, namely P. brunneolus, P. divaricatus, P. formosus, and P. saturatus. This is the first report of P. niveus as a parasite of N. ribisnigri in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ITS sequencing and phylogenetic analysis indicated that the isolate (PaePR) obtained in this study was clustered with its teleomorph, B. nivea. Samson et al (2009) verified by phylogenetic analyses that the genus Byssochlamys includes nine species, five of which form teleomorphs, i.e., B. fulva, B. lagunculariae, B. nivea, B. spectabilis and B. zollerniae, whereas four are asexual, namely P. brunneolus, P. divaricatus, P. formosus, and P. saturatus. This is the first report of P. niveus as a parasite of N. ribisnigri in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Hypocreales (Ascomycota) can be important for reducing aphid populations (Steinkraus, 2006). According to Samson et al (2009) the genus Byssochlamys is morphologically well defined and characterized by almost naked ascomata in which croziers and globose asci are formed with ellipsoidal ascospores. All Byssochlamys species have a Paecilomyces anamorph that belongs to the Paecilomyces sect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been isolated from P. expansum [79] (P. leucopus [80], P. vulpinum [17] (P. claviforme [68]), P. griseofulvum [79] (P. patulum [69]), P. carneum, P. clavigerum, P. concentricum, P. coprobium, P. dipodomyicola, P. glandicola, P. gladioli, P. marinum, P. paneum, P. sclerotigenum [81], P. cyclopium [82], P. granulatum (P. divergens [83]), P. melinii, P. lapidosum [82], P. aurantiogriseum, P. canescens, P. chrysogenum, P. roqueforti, P. variabile [78], P. purpurogenum [84], Aspergillus clavatus, A. giganteus, A. longivesica [85], A. terreus [86], Byssochlamys fulva, B. nivea and Paecilomyces saturatus [87,88]. PAT has been detected in apples and apple products, and occasionally in other fruits such as pears, apricots, peaches and grapes [77].…”
Section: Producing Fungal Speciesmentioning
confidence: 99%
“…The reports of patulin production by P. roqueforti (Cakmakci et al, 2015;Chunmei et al, 2013;Erdogan et al, 2003;Leistner and Pitt, 1977;Malekinejad et al, 2015;Müller and Amend, 1997;Olivigni and Bullerman, 1978;Paterson et al, 2003;Steiman et al, 1989;Vismer et al, 1996) appear to be caused by misidentifications, because the closely related species P. carneum and P. paneum both produce patulin (Boysen et al, 1996). Paecilomyces fulvus (formerly Byssochlamyes fulva), Puel et al, 2007), but these species all have heat resistant ascospores (Samson et al, 2009), and thus may survive in pasteurised fruit juices and produce patulin (Rice et al, 1977;Sant' Ana et al, 2010). Paecilomyces niveus and Penicillium paneum can grow in substrates with a high concentration of acetic acid and thus can also be found in silage, and may produce patulin there (Gallo et al, 2015;O'Brien et al, 2006;Scurti et al, 1973).…”
Section: Penicillium Miczynskiimentioning
confidence: 99%